2007
DOI: 10.6028/jres.112.024
|View full text |Cite
|
Sign up to set email alerts
|

Holmium oxide glass wavelength standards

Abstract: Holmium oxide glass has been used as a wavelength standard for over four decades. These standards have shown insignificant spectral variation from batch to batch and from one manufacturer to another. The National Institute of Standards and Technology (NIST) has certified and recertified holmium oxide glass samples for over four decades. Over this period of time there has been no recorded instance of a spectral shift of the certified bands for any of the samples measured. Moreover, these samples are known to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Absorbance spectra covering 400-850 nm were measured at room temperature for 10 lM dye solutions using a 1 cm path length and a Beckman DU-650 spectrophotometer having a spectral bandwidth of 2 nm full-width at half-maximum (FWHM). Wavelength accuracy of the instrument was verified to be AE1 nm using a NIST traceable holmium oxide absorbance standard [16] (Starna Inc). All dye solutions were prepared in dimethyl sulfoxide (DMSO), a solvent that could be modeled without including explicit solventmolecule interactions [17].…”
Section: Methodsmentioning
confidence: 99%
“…Absorbance spectra covering 400-850 nm were measured at room temperature for 10 lM dye solutions using a 1 cm path length and a Beckman DU-650 spectrophotometer having a spectral bandwidth of 2 nm full-width at half-maximum (FWHM). Wavelength accuracy of the instrument was verified to be AE1 nm using a NIST traceable holmium oxide absorbance standard [16] (Starna Inc). All dye solutions were prepared in dimethyl sulfoxide (DMSO), a solvent that could be modeled without including explicit solventmolecule interactions [17].…”
Section: Methodsmentioning
confidence: 99%
“…There should be three strong distinct peaks between 440 and 460 nm. Peaks should be clearly distinguished at 241.5, 279.3, 287.6, 333.8, 360.8, 385.8, 418.5, 453.4, 459.9, 536.4, and 637.5 ± 0.2 nm (Allen, 2007). Any peaks appearing below 225 nm indicate stray light in the instrument.…”
Section: Calibrationsmentioning
confidence: 99%
“…NIST has asserted that holmium oxide glass wavelength standards "have shown insignificant spectral variation from batch to batch and from one manufacturer to another", that over four decades "there has been no recorded instance of a spectral shift of the certified bands for any of the samples measured", and that the samples "are known to be robust and relatively insensitive to a normal range of temperature and humidity". [13] It is further stated that "holmium oxide is inherently more stable than most instruments [used to measure the absorption bands]" and can be considered as an intrinsic standard. The standards vendor claims that a study of their product by the National Research Council of Canada has demonstrated no shift in absorbance values for at least 8 years.…”
Section: Component Propertiesmentioning
confidence: 99%